Taxonomy and Phylogeny of the Fomitopsis pinicola Complex With Descriptions of Six New Species From East Asia - Liu, Shun; Han, Mei-Ling; Xu, Tai-Min; Wang, Yan; Wu, Dong-Mei; Cui, Bao-Kai (Frontiers in Microbiology, 2021)
Fomitopsis pinicola is a common brown-rot fungal species in northern hemisphere, and it grows on many different gymnosperm and angiosperm trees. Recent studies showed that it is a species complex and three species from North America and one species from Europe were recognized in this complex. In the current study, six new species in Fomitopsis pinicola complex are discovered from East Asia based on morphological characters and phylogenetic analyses inferred from sequences data of the internal transcribed spacer (ITS) regions, the second subunit of RNA polymerase II (RPB2) and the translation elongation factor 1-α gene (TEF). Detailed descriptions of the six new species are provided. Our results also indicated that species of the F. pinicola complex from East Asia usually have limited distribution areas and host specialization.